Apendisitis Akut Pada Pasien Dewasa: Ulasan Singkat - Fachmi Aditya; Satria, Muhammad (Medula, 2024)
Acute appendicitis is an inflammatory condition that occurs within 24 hours in the vermiform appendix which is usually triggered by obstruction of the outlet of the appendix and in adult patients the obstruction is caused by lymphoid hyperplasia. The typical clinical manifestation that appears is periumbilical pain which then migrates to the right lower quadrant. Typical physical examination is tenderness at the McBurney point, Rovsing sign, obturator sign and psoas sign. The most important supporting examination is a complete blood test which indicates the presence of leukocytosis. Imaging modalities are performed if the clinical diagnosis is not yet established and to determine the size of the inflamed appendix. The imaging modality often chosen is abdominal ultrasound because it is cheap, easy and suitable for pregnant patients and children. Abdominal ultrasound will show an anteroposterior appendiceal diameter of >6 mm with an abnormal increase in peri-appendiceal fat echogenicity. After the diagnosis of acute appendicitis is made, the next step in treatment is to consider whether an appendectomy, either laparoscopic or open laparotomy, is needed. In addition, administering empirical broad-spectrum antibiotics such as a combination of cephalosporins or fluroquinolones with metronidazole is also important in this case.